Drivers to Adolescent Pregnancy - Gapulan, Dyan (JPAIR Multidisciplinary Research, 2017)
In the local state college in Negros Occidental, Philippines, data from the Guidance Office confirmed an increased cases in adolescent pregnancy in the last three years. With the use of the phenomenological approach utilizing in-depth interview, this study looked into the circumstances in the lives of the pregnant adolescent students which led to their early pregnancy. These pregnant adolescents were enrolled during the 2nd semester of the academic year 2015-2016 in the State College in Negros Occidental. Purposive sampling was employed to identify the participants of this research. Exploring the participants’ narratives, common patterns or themes were observed. Circumstances which have led to their pregnancy are divided into 2 broad themes. Inherent Factors which are in their search for love, some life-changing decisions and their lack of awareness about sex. Adventitious Factors, on the other hand, are the family’s social interaction and being deceived by her partner. The results were used as a basis for formulating an intervention program for the pregnant adolescents, which was intended to develop some of their necessary life skills and also implement a massive campaign regarding adolescent sexuality as identified in this research.